Use of Triplex PCR for Rapid Detection of PVL and Differentiation of MRSA from Methicillin Resistant Coagulase Negative Staphylococci - Nagarajan Abimanyu (Journal of Clinical and Diagnostic Research, 2013)
ABSTRACT Introduction: Methicillin-Resistant Staphylococcus aureus (MRSA) has become a major public health problem in both hospitals and communities. Panton – Valentine Leucocidin (PVL) has been reported to be an important marker for the highly pathogenic community acquired S. aureus infections. A rapid detection of these MRSA is very important for its treatment. The specific detection of MRSA is always a problem due to the prevalence of methicillin resistance among the coagulase negative Staphylococci. Hence, this study was done to develop a rapid triplex PCR for the detection of PVL positive MRSA and for the simultaneous differentiation of MRSA from Coagulase Negative Staphylococci (CoNS). Materials and Methods: We developed a triplex PCR for the specific detection of PVL positive Community Acquired (CA) – MRSA and for its simultaneous differentiation from the coagulase negative Staphylococci. We used PCR for targeting the fem A gene which is specific for S. aureus, mecA which is specific for methicillin-resistance and luk - PV which is specific for the PVL toxin. The method was evaluated with a total of 100 clinical isolates of Staphylococcus spp. Results: The triplex PCR was successfully standardized by using the reference strains and it was evaluated by using clinical strains. The method was found to be rapid, highly sensitive (100%), specific (99%) and cost effective. Conclusion: Triplex PCR can be used as a diagnostic tool for the detection of the highly pathogenic strains of CA-MRSA.